Prevalence of noise-induced hearing loss in drivers - Lopes, Andréa Cintra; Otowiz, Vanessa Guioto; Lopes, Patrícia Monteiro de Barros; Lauris, José Roberto Pereira; Santos, Cibele Carméllo (International Archives of Otorhinolaryngology, 2012)
Introduction: Work-related hearing loss is one of the most common occupational illness progresses over the years of noise exposure associated with the work environment, may cause damage to undertake physical activity, the individual's physiological and mental besides causing hearing damage irreversible interfering with communication and quality of life. With high prevalence of male evaluates which is the second leading cause of hearing loss. Since there is no medical treatment for this type of hearing loss, it is evident the importance of preventive and conferences aimed at preserving hearing and health as a whole.Objective: To assess the prevalence of hearing loss in audiometry admission of drivers.Methods: Retrospective study. By 76 charts of professional drivers in leased transport companies. We analyzed data from specific interview and pure tone audiometry.Results: The prevalence of abnormal tests was 22.36% with the lowest thresholds for tritonal average of 3,000, 4,000 and 6,000 Hz. The higher the age, the higher thresholds.Conclusion: This study has highlighted the occurrence of hearing in the absence of complaints. Considering that PAIR is preventable, justifies the importance of coordinated and multidisciplinary involving not only health teams and safety, but also the institutions involved in preserving the health of workers, as the team SESMET, unions or prosecutors.
Keywords: noise; pure tone audiometry; hearing loss